Google Meet Application and Media Power Points to Improve IPA Learning Results - Komalasari, Essa Ratih (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The background of this research is the low courage of the science learning outcomes in grade V SDN 02 Pekuncen. The purpose of this research is to improve the learning outcomes of students in the science muple. The method used in learning is through the Google Meet application using Power Point media. Classroom Action Research is carried out in three cycles, namely planning, implementing, observing, and reflecting. In cycle I there is an increase in learning outcomes from cycle as much as 38%, from cycle 1 to cycle II experienced a 53% increase in learning outcomes and cycle II to cycle III as much as 97%. This shows that the use of the Google application to meet the Power Point media can improve student learning outcomes, especially in Class V science muple at SDN 02 Pekuncen.